The effect of Kinship marriages on the Public Hospitals in Pakistan - Asif, Shahbaz; Miklánek, Tomáš; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
The study summarized the effect of cousin marriages on the public health care system in terms of genetic diseases. Direct costs were estimated as well the social and psychological impact of genetic diseases on public health care.
Vedoucí práce: Tomáš Miklánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses